1996
DOI: 10.1016/0275-5408(95)00017-8
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the keratoconic cornea using computerised corneal mapping and ultrasonic measurements of corneal thickness

Abstract: Reports indicate the presence of up to three independent cone shapes in keratoconus (round/oval/global) but the preponderance of one cone over another is unclear. This work evaluates keratoconic corneal topography and corneal thickness using videokeratoscopy and ultrasound pachometry, respectively. An EyeSys videokeratoscope (VKS) (EyeSys Laboratories, Houston, TX, USA) was used to assess the topography of 54 keratoconic eyes (27 subjects) and 27 age-matched normals. In addition, ultrasonic pachometry measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…26 In DUSKS, 88.5% were found to exhibit bilateral keratoconus, usually asymmetrical in presentation (P ¼ 0.005). Fleischer's-ring was the most frequently observed corneal sign (86-89%) as reported previously 2,27 followed by Vogt's striae (67-68%) and corneal scarring (21-20%) at review 1 and 2, respectively. Notably, corneal slit-lamp signs cannot be relied upon solely as diagnostic criteria as approximately 15% of eyes exhibited no corneal signs despite pathognomonic topographic signs of keratoconus.…”
Section: Discussionsupporting
confidence: 76%
“…26 In DUSKS, 88.5% were found to exhibit bilateral keratoconus, usually asymmetrical in presentation (P ¼ 0.005). Fleischer's-ring was the most frequently observed corneal sign (86-89%) as reported previously 2,27 followed by Vogt's striae (67-68%) and corneal scarring (21-20%) at review 1 and 2, respectively. Notably, corneal slit-lamp signs cannot be relied upon solely as diagnostic criteria as approximately 15% of eyes exhibited no corneal signs despite pathognomonic topographic signs of keratoconus.…”
Section: Discussionsupporting
confidence: 76%
“…[34][35][36][37][38][39] Mandell and Polse 34 pioneered the investigations of corneal thickness profile in a study using a modified Haag-Streit optical pachymeter with an electronic recording system to document the variation in thickness over the horizontal meridian measured at different angles. In their study, the difference between the central and the peripheral measurements was much greater in eyes with keratoconus; it was most significant at the 35-degree position, where the authors found a difference greater than 0.085 mm as pathognomonic of keratoconus.…”
Section: Discussionmentioning
confidence: 99%
“…36 Regional measurements and mapping of corneal thickness are also possible using ultrasound computed tomography single-point measurements. 38,39 However, ultrasound computed tomography does not provide data from the true thinnest point and the angulation of the probe might also account for error in the case of regional thickness measurements. In addition, ultrasound computed tomography does not allow precise localization, even for the central point, and proper training is required for reproducible results.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43] In our study an empirical combination of corneal apex power 44 and thickness was used. 45 Therefore, in this context the in vivo confocal microscopy data may not always be readily correlated with the small number of published studies on the topic. Erie et al 35 observed that the decrease in the keratocyte density, in a study of mild to moderate keratoconus was only in association with contact lens wear.…”
Section: 39mentioning
confidence: 99%